2017
DOI: 10.3847/1538-4357/aa634a
|View full text |Cite
|
Sign up to set email alerts
|

An r-process Enhanced Star in the Dwarf Galaxy Tucana III*

Abstract: Chemically peculiar stars in dwarf galaxies provide a window for exploring the birth environment of stars with varying chemical enrichment. We present a chemical abundance analysis of the brightest star in the newly discovered ultra-faint dwarf galaxy candidate Tucana III. Because it is particularly bright for a star in an ultra-faint Milky Way satellite, we are able to measure the abundance of 28 elements, including 13 neutron-capture species. This star, DES J235532.66−593114.9 (DES J235532), shows a mild enh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 82 publications
9
82
0
Order By: Relevance
“…Incorporating this ejecta into ∼ 10 3 to 10 4 M of stars formed after the merger would produce the observed [Eu/H] ratios, assuming a star formation efficiency of ∼ 1% and no loss of r-process metals. This mass is comparable to that of the lowest-mass dwarf galaxies known today, including Reticulum II (Ji et al 2016c) and Tucana III (Hansen et al 2017), which are known to contain r-process-enhanced stars. There is considerable scatter among the [Eu/H] ratios of individual stars in these systems (−1.6 ≤ [Eu/H] ≤ −0.3), and the average [Eu/H] ratio of stars in a system may provide a more meaningful measure than that from any one star.…”
Section: The Environment Of Hd 222925mentioning
confidence: 66%
“…Incorporating this ejecta into ∼ 10 3 to 10 4 M of stars formed after the merger would produce the observed [Eu/H] ratios, assuming a star formation efficiency of ∼ 1% and no loss of r-process metals. This mass is comparable to that of the lowest-mass dwarf galaxies known today, including Reticulum II (Ji et al 2016c) and Tucana III (Hansen et al 2017), which are known to contain r-process-enhanced stars. There is considerable scatter among the [Eu/H] ratios of individual stars in these systems (−1.6 ≤ [Eu/H] ≤ −0.3), and the average [Eu/H] ratio of stars in a system may provide a more meaningful measure than that from any one star.…”
Section: The Environment Of Hd 222925mentioning
confidence: 66%
“…This mechanism could enhance halo stars in r-process elements already at early times, when the metallicity of the halo stars is low and many building blocks of the stellar halo still have shallow potential wells from which NS binaries easily escape after receiving a standard kick velocity. This scenario is supported by the recent observation of a only mildly r-process enhanced star in the ultra-faint dwarf galaxy Tucana III (Hansen et al 2017), contrary to the highly r-process enhanced stars observed in Ret II.…”
Section: Summary and Discussionmentioning
confidence: 58%
“…It does not present significant s-process or r-process enrichment like the stars in Ret II (Ji et al 2016c) or Tuc III (Hansen et al 2017). The upper limit of Eu found in DES J025535-540643 ([Eu/Fe] < +1.02) excludes it from being an r-II star (defined as [Eu/Fe]>+1.0) but does not exclude the possibility that it is an r-I star (defined as [Eu/Fe]>+0.3), where these definitions are taken from Beers & Christlieb (2005).…”
Section: Resultsmentioning
confidence: 99%
“…Four DES-discovered ultrafaint dwarfs have been chemically studied in detail to date: Ret II (Ji et al 2016a;Roederer et al 2016), Tuc II (Ji et al 2016b), Tuc III (Hansen et al 2017), and now Hor I. In each case (with the possible exception of Tuc II), the brightest confirmed member stars show an unexpected and peculiar abundance pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation